Variasi Bahasa dalam Komentar pada Media Sosial Instagram Nur Rofiah - Muthia Selvi Elsa; Salma Nur Aisyah; Syahrul Ramadhan; Elfia Sukma; Norliza Binti Jamaluddin (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
Language plays a crucial role in human daily activities. In using language, people cannot avoid using various language varieties that reflect the context and social background of the speakers. Therefore, the importance of sociolinguistic studies has a major influence in recognizing language variations that emerge in communication, especially in the digital space. This study aims to examine the language variations used in comments on the Instagram account of Nur Rofiah, a public figure who is known to be active in voicing gender justice issues from an Islamic perspective. This study uses a sociolinguistic approach to identify forms of language variation and the social factors that influence them. Data were collected through documentation methods on comments on a number of Nur Rofiah's uploads that were considered representative. The results of the study show that there are various language variations, including variations based on dialect, level of formality, use of mixed language (code-mixing), and emotive varieties that reflect the identity and social background of the user. In addition, it was found that factors such as age, gender, educational background, and ideological orientation also influence language choices in digital interactions. These findings indicate that social media is not only a communication space, but also an arena for expressing people's social and ideological identities.